Temporal mandibular joint chondrocalcinosis (tophaceous pseudogout) diagnosed by ultrasound‐guided fine‐needle aspiration. Issue 8 (25th March 2019) - Fan, Jun; Heimann, Alan; Wu, Maoxin
Abstract : Tophaceous pseudogout is a calcium pyrophosphate dihydrate crystal (CPPD) deposition disease that frequently affects elderly patient in the temporomandibular joint (TMJ). A diagnosis of CPPD deposition disease in the TMJ is challenging due to its mimicking of other benign and malignant entities. Surgical exploration followed by histologic examination is by far the most frequently used diagnostic modality. We present a case of an 87‐year‐old female who presented with a right TMJ mass. A final diagnosis of tophaceous pseudogout was made on cellular material obtained by ultrasound‐guided fine‐needle aspiration (US‐guided FNA). Based on our case and current available literature, ultrasound‐guided FNA is a reliable tool for diagnosing tophaceous pseudogout of the TMJ.